Teacher’s Strategies and Classroom Management Techniques in Teaching English at SMP Inklusi TPA Jember - Nostalgianti Citra Prystiananta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The research aims at explaining the teacher’s strategies and classroom management techniques applied in teaching English to mental retardation students at SMP Inklusi TPA Jember. This is a descriptive qualitative research. The subject of the research was an English teacher at SMP Inklusi TPA Jember. The data were collected through a non-participant observation and interview. The data were analyzed through identification, classification, data reduction, and description. The findings were: 1) the teacherused three kinds of strategies, i.e. imitation and modeling strategy, demonstration strategy, and active strategy with imitation and modeling strategy as the most used; 2) from 7 classroom management techniques listed by Sarosdy, Bencze, Poor and Vadnay (2016), there were only 5 techniques applied by the teacher including showing respect for students, showing professionalism, applying class techniques, applying positive attitude of teacher’s role and knowing the students. Keywords: Mental Retardation, Teachers Strategies, Classroom Management, Teaching Disable